Falsafah dan Kurikulum Pendidikan Islam Menurut Pandangan Tokoh Ilmuwan Islam: Imam al-Qabisi - Muhamad Amirul Mohd Nor; Muhammad Zulazizi Mohd Nawi (USIM Press, 2024)
Vol. 5 No. 1 (2020): Jurnal Sains Insani